Recursive Least-Squares Filtering of Pseudorange Measurements - Le, A.; Teunissen, Peter (ECN, 2006)
Code pseudorange measurement noise is one of the major error sources in Precise Point Positioning. A recursive least-squares solution with proper functional and stochastic modelling would help to exploit in addition the ultra high precision of the carrier phase measurement. Analyses of different methods, including phase smoothed, phase connected and phase adjusted pseudorange algorithm, will show that the phase adjusted pseudorange algorithm is statistically optimal. Static and kinematic experiment results also support the conclusion with more than 30% of improvement by going from the phase smoothed to the phase adjusted algorithm.